Reprint of: A healthy island blue space: From space of detention to site of sanctuary. (September 2015) - Kearns, Robin A.; Collins, Damian; Conradson, David
Abstract: Island blue spaces are associated with restorative potential, but few studies examine this proposition when an island׳s use has changed over time. We examine Rotoroa Island (near Auckland, New Zealand) where, for almost a century, the Salvation Army ran an alcohol treatment facility. The island׳s relative isolation was central to its mixed therapeutic and carceral roles. Following change in treatment ideologies, the facility closed in 2005. It subsequently re-opened as a reserve for recreation, remembrance and environmental restoration. Our analysis focuses on the enabling resources at Rotoroa across these two eras, in the context of different constructions of healthy island blue space.